Posttraumatic carotid-cavernous fistula: Pathogenetic mechanisms, diagnostic management and proper treatment. A case report - Marín-Fernández, Ana-Belén (J Clin Exp Dent, 2016)
Carotid-cavernous fistulas are an uncommon diseases characterized by abnormal communications between arteries and veins located in the cavernous sinus. According with Barrow´s classification they could be divided in two groups: direct and indirect. The typical symptoms showed by theses pathologies are: pulsating exophthalmos and orbital blow. The present study describes a case of direct posttraumatic carotid-cavernous fistula in a 26 years old man. Furthermore, we present the images that we used to make the diagnosis. In this light, we decided to treat this case with endovascular approach after considering several therapeutic options. The aim of the present report is twofold. First, we examine the importance of the proper management of the direct posttraumatic carotid-cavernous fistula. Second, we describe this rare syndrome with the goal of proposing suitable treatments. Key words:Carotid cavernous fistulas, pulsating exophthalmos, orbital blow, endovascular approach, Barrow´s classification.